New insights in hepatocellular carcinoma: from bench to bedside - De Minicis, Samuele (AME Publishing Company, 2013)
Hepatocarcinogenesis is a multistep process involving different genetic alterations that ultimately lead to malignant transformation of the hepatocyte. The liver is one of the main targets for different metastatic foci, but it represents an important and frequent locus of degeneration in the course of chronic disease. In fact, Hepatocellular carcinoma (HCC) represents the outcome of the natural history of chronic liver diseases, from the condition of fibrosis, to cirrhosis and finally to cancer. HCC is the sixth most common cancer in the world, some 630,000 new cases being diagnosed each year. Furthermore, about the 80% of people with HCC, have seen their clinical history developing from fibrosis, to cirrhosis and finally to cancer. The three main causes of HCC development are represented by HBV, HCV infection and alcoholism. Moreover, metabolic disease [starting from Non Alcoholic Fatty Liver Disease (NAFLD), Non Alcoholic Steatohepatitis (NASH)] and, with reduced frequency, some autoimmune disease may lead to HCC development. An additional rare cause of carcinogenetic degeneration of the liver, especially developed in African and Asian Countries, is represented by aflatoxin B1. The mechanisms by which these etiologic factors may induce HCC development involve a wide range of pathway and molecules, currently under investigation. In summary, the hepatocarcionogenesis results from a multifactorial process leading to the common condition of genetic changes in mature hepatocytes mainly characterized by uncontrolled proliferation and cell death. Advances in understanding the mechanism of action are fundamental for the development of new potential therapies and results primarily from the association of the research activities coming from basic and clinical science. This review article analyzes the current models used in basic research to investigate HCC activity, and the advances obtained from a basic and clinical point of view.